Pursuit of the universal : 12th Conference on Computability in Europe, CiE 2016, Paris, France, June 27-July 1, 2016, Proceedings /: 12th Conference on Computability in Europe, CiE 2016, Paris, France, June 27-July 1, 2016, Proceedings. (2016) - Unknown
No abstract available